Expert Knowledge-based Inspection Systems : Inspection, Diagnosis, and Repair of the Building Envelope /: Inspection, Diagnosis, and Repair of the Building Envelope. (2020) - de Brito, Jorge; Pereira, Clara; Silvestre, José D; Flores-Colen, Inês
No abstract available